1998
DOI: 10.1016/s0168-0102(98)00064-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of movement predictability on cortical motor activation

Abstract: Humans have the ability to make motor responses to unpredictable visual stimuli, and do so as a matter of course on a daily basis. We used functional magnetic resonance imaging (fMRI) to examine the neural substrate of this behavior in six cortical motor areas. We found that five of these areas (premotor, cingulate, supplementary motor area, pre-supplementary motor area, and superior parietal lobule) showed increased activation in association with an unpredictable behavior compared to a predictable one; only t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
50
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 76 publications
(68 reference statements)
6
50
1
Order By: Relevance
“…None explained the asymmetry found in the present study. We suggest that the lateralization may be a consequence of normal left hemisphere dominance in motor function [Dassonville et al, 1998;Kawashima et al, 1993].…”
Section: Discussionmentioning
confidence: 83%
“…None explained the asymmetry found in the present study. We suggest that the lateralization may be a consequence of normal left hemisphere dominance in motor function [Dassonville et al, 1998;Kawashima et al, 1993].…”
Section: Discussionmentioning
confidence: 83%
“…The posterior boundary was halfway between the extension of the central and precentral sulci onto the medial surface, and the anterior boundary was defined by the vertical line drawn from the anterior commissure. 16 Because of a large within-subject variability in the BOLD signal, a normalized index, the laterality index (LI), was used to determine any shift in the symmetry of cortical activation between the 2 hemispheres for the ROIs as a function of intervention. 13,14 This index is expressed as (CϪI)/(CϩI), where C is the active voxel count for the ROIs in the hemisphere contralateral to the leg performing the movement and I is the active voxel count for the corresponding region in the hemisphere ipsilateral to the performing leg.…”
Section: You Et Al Virtual Reality-induced Cortical Reorganizationmentioning
confidence: 99%
“…Although the control of movement is one of the clearest hemispherically lateralized functions in the brain (Dassonville et al, 1998), human functional neuroimaging studies of hand motor control commonly report bilateral activation in the primary motor cortex (Hlustik et al, 2002;Solodkin et al, 2001). We also compared BOLD-fMRI responses at two different stimulation intensities and found that highintensity motor cortex stimulation (120% rMT) was associated with significantly increased activation compared to lower intensity (100% rMT) stimulation (Bohning et al, 2000), on the placebo day only.…”
Section: Bold Response To Tms Over the Motor Cortexmentioning
confidence: 94%